Language Mediated Concept Activation in Bilingual Memory Facilitates Cognitive Flexibility - Kharkhurin, Anatoliy V. (Frontiers in Psychology, 2017)
This is the first attempt of empirical investigation of language mediated concept activation (LMCA) in bilingual memory as a cognitive mechanism facilitating divergent thinking. Russian-English bilingual and Russian monolingual college students were tested on a battery of tests including among others Abbreviated Torrance Tests for Adults assessing divergent thinking traits and translingual priming (TLP) test assessing the LMCA. The latter was designed as a lexical decision priming test, in which a prime and a target were not related in Russian (language of testing), but were related through their translation equivalents in English (spoken only by bilinguals). Bilinguals outperformed their monolingual counterparts on divergent thinking trait of cognitive flexibility, and bilinguals’ performance on this trait could be explained by their TLP effect. Age of second language acquisition and proficiency in this language were found to relate to the TLP effect, and therefore were proposed to influence the directionality and strength of connections in bilingual memory.